2022
DOI: 10.3390/v14081611
|View full text |Cite
|
Sign up to set email alerts
|

Is the HTLV-1 Retrovirus Targeted by Host Restriction Factors?

Abstract: Human T cell leukemia virus type 1 (HTLV-1), the etiological agent of adult T cell leukemia/lymphoma (ATLL) and of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), was identified a few years before Human Immunodeficiency Virus (HIV). However, forty years later, our comprehension of HTLV-1 immune detection and the host immune responses to HTLV-1 is far more limited than for HIV. In addition to innate and adaptive immune responses that rely on specialized cells of the immune system, host cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…The COVID-19 pandemic, caused by SARS-CoV-2, has been the most challenging public health crisis in over a century. Although several therapeutic treatments are available, a better understanding of innate host cell restriction factors that can prevent viral infection could provide critical information for developing broad-spectrum therapeutics to prevent or treat COVID-19, as well as other emergent or established viral diseases, for instance, those caused by Zika, Ebola, influenza, HIV or dengue viruses ( 1 6 ). One such viral restriction factor, the integral membrane zinc metalloprotease ZMPSTE24, is the subject of this study.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic, caused by SARS-CoV-2, has been the most challenging public health crisis in over a century. Although several therapeutic treatments are available, a better understanding of innate host cell restriction factors that can prevent viral infection could provide critical information for developing broad-spectrum therapeutics to prevent or treat COVID-19, as well as other emergent or established viral diseases, for instance, those caused by Zika, Ebola, influenza, HIV or dengue viruses ( 1 6 ). One such viral restriction factor, the integral membrane zinc metalloprotease ZMPSTE24, is the subject of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Restriction factors are either constitutively expressed or induced by mediators of innate immunity such as type I IFN (interferon-stimulated genes or ISGs) to recognize and inhibit viral replication at multiple steps of the viral infection cycle, in a cell-autonomous manner [ 61 , 62 ]. RFs were originally discovered in the HIV research field, and since then, several RFs have been identified, belonging to diverse protein families that drive antiviral responses through multiple mechanisms [ 62 , 63 , 64 ]. Recent studies, described below, have highlighted the role of several restriction factors involved in the protection against HTLV-1 infection and their modes of action ( Figure 2 ).…”
Section: Htlv-1 Restriction Factorsmentioning
confidence: 99%
“…Studies pertaining to HTLV-1 restriction factors are rather limited with the majority of them discovered through studies in HIV-1 infection. The role of restriction factors in HTLV-1 infection has been extensively reviewed elsewhere ( 23 , 24 ) and is summarized briefly in Table 1 .…”
Section: Immune Escape Mechanisms Used By Htlv-1-infected Cells For P...mentioning
confidence: 99%
“…This process is called immune surveillance ( 18 ) and is carried out by both the innate and acquired immune system. Immune response to HTLV-1 has been extensively reviewed elsewhere ( 19 22 ) with most of the recent work focusing on the innate immune responses, including retroviral restriction factors ( 23 , 24 ) and chemokines ( 25 ). HTLV-1 mainly infects CD4 + T cells, which are one of the major players of the cell-mediated immune response primarily carried out by T cells ( 26 ).…”
Section: Introductionmentioning
confidence: 99%